2016
DOI: 10.1589/jpts.28.1208
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between self-reported and performance-based measures of functional capacity in individuals with chronic stroke

Abstract: [Purpose] The aim of this study was to investigate the associations between self-reported and valid performance-based measures of functional capacity in individuals with chronic stroke. [Subjects and Methods] Self-reported measures of functional capacity of 31 individuals with chronic stroke were assessed by the Duke Activity Status Index scores, whereas performance-based measures were assessed by the distance covered (in meters) and oxygen consumption (relative oxygen consumption, in ml·kg−1·min−1) during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In most cases, the walking function of patients is reported to be affected by neurological impairment, and this is apparently what induces problems with asymmetrical gait. Hence, recovery of walking function following stroke should be one of the main goals of rehabilitation10 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, the walking function of patients is reported to be affected by neurological impairment, and this is apparently what induces problems with asymmetrical gait. Hence, recovery of walking function following stroke should be one of the main goals of rehabilitation10 ) .…”
Section: Discussionmentioning
confidence: 99%
“…16 Functional capacity was assessed with the Duke Activity Status Index (DASI). 17,18 The tests and questionnaires were administered by trained researchers.…”
Section: Methodsmentioning
confidence: 99%
“…The results of this study answered the main question, since it was found that the individuals with stroke with higher levels of physical activity demonstrated higher functional capacity, i.e., present higher METS energy cost (in METS). Recently, the study of Polese et al [11] was the first to use the DASI for the assessment the functional capacity of a sample of 31 chronic stroke individuals, and found a mean DASI score of 27.3. This value was similar to that observed in the present study for the moderately active group, who showed a mean DASI score of 32.0 (SD 11.5).…”
Section: Discussionmentioning
confidence: 99%
“…Since functional capacity is related to physiological variables, i.e., oxygen consumption, the use of simple and reliable measures is crucial within clinical environments. Although the Duke Activity Status Index (DASI) was originally developed for the evaluation of patients with cardiovascular diseases [10], it has also been used with stroke individuals, since its scores were shown to be highly related to physical performance measures [11].…”
Section: Introductionmentioning
confidence: 99%